Impact of ethanol vapor treatment on the quality of water bamboo (Zizania caduciflora L.) shoots during cold storage. Issue 5 (11th March 2022) - Dong, Guijun; Wang, Chunfang; Liu, Hongru; Liu, Chenxia; Qiao, Yongjin
Abstract: This study evaluated the effect of ethanol vapor treatments on the physicochemical characteristics and quality of postharvest water bamboo shoots (WBS) ( Zizania caduciflora L.). WBS were treated with ethanol vapor at doses of 0 (control), 500, 750, and 1000 μl/L at 0 ± 1°C for 35 days. The fruit were evaluated for weight loss, firmness, color, total soluble solids, soluble sugars, malondialdehyde, lignin, and lignification‐related enzyme activities. The results revealed that all ethanol treatments could inhibit the weight loss and softening of WBS, reduce the reduction of soluble solids and soluble sugars content, inhibit the lignification‐associated enzymes peroxidase and phenylalanine ammonia lyase activities, and reduce the synthesis of lignin. Among them, the 750 μl/L ethanol vapor treatment had a significant effect on all tested parameters and maintained the storage quality of WBS better than other treatments. Practical applications: Water bamboo shoot is a nutritionally rich aquatic vegetable. However, its quality deteriorates rapidly after harvest due to wilting, softening, and lignification. The ethanol vapor treatment in this study significantly reduced the softening and lignification of WBS. The ethanol vapor treatment is simple and has less residue, which is effective in maintaining the fruit quality and reducing the nutritional loss of WBS after harvest. It is a safe and environmentally friendly preservation method for WBS.